2003
DOI: 10.1289/ehp.6105
|View full text |Cite
|
Sign up to set email alerts
|

Increased influence of genetic variation on PON1 activity in neonates.

Abstract: PON1 (paraoxonase-1) detoxifies organophosphates by cleavage of active oxons before they have a chance to inhibit cholinesterases. The corresponding gene PON1 has common polymorphisms in both the promoter (-909, -162, -108) and the coding region (L55M, Q192R). The five PON1 genotypes were determined for maternal blood (n = 402) and cord blood (n = 229) as part of a study of the effects of organophosphate pesticide exposure on infant growth and neurodevelopment. PON1 enzymatic activities were determined for a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
89
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 33 publications
17
89
0
2
Order By: Relevance
“…27,41 These phenotypic correlates of PON1 genotypes are even more prominent in neonates than in adults, and this trend may likely extend into prenatal life. 43 Hence, although we cannot exclude the existence of mutations in noncoding regions of PON1 or in nearby loci, the most parsimonious explanation for our findings is that a reduction in paraoxonase activity and/or amount produced by these SNPs may by itself confer autism vulnerability in one ethnic group only. PON1 encodes the human HDL-associated paraoxonase, which, in addition to hydrolyzing OP compounds, physiologically reduces LDL and HDL oxidation, and hydrolyzes platelet-activating factor (PAF).…”
Section: Markersmentioning
confidence: 77%
“…27,41 These phenotypic correlates of PON1 genotypes are even more prominent in neonates than in adults, and this trend may likely extend into prenatal life. 43 Hence, although we cannot exclude the existence of mutations in noncoding regions of PON1 or in nearby loci, the most parsimonious explanation for our findings is that a reduction in paraoxonase activity and/or amount produced by these SNPs may by itself confer autism vulnerability in one ethnic group only. PON1 encodes the human HDL-associated paraoxonase, which, in addition to hydrolyzing OP compounds, physiologically reduces LDL and HDL oxidation, and hydrolyzes platelet-activating factor (PAF).…”
Section: Markersmentioning
confidence: 77%
“…Concentrations were imputed for missing values (5); metabolites were then summed (as nm/L) to obtain ⌺DEP (DEDP, diethylphosphate, diethylthiophosphate), ⌺DMP (DMDP, dimethylphosphate DMTP), and ⌺DAP (⌺DEP ϩ ⌺DMP). PON1 activity was determined as previously reported in plasma (mol/min/ mL) using phenylacetate as substrate (15). BuChe activity (mol/min/mL) was determined by the method of Ellman et al (16) using 1 mmol/L butyrylthiocholine as substrate in 50 mmol/L phosphate buffer, pH 8.0, at 25°C, following absorbance at 412 nm.…”
Section: Methodsmentioning
confidence: 99%
“…PONQ192R was genotyped (n ϭ 389) as reported (17). This PON1 variant was chosen because its maternal phenotypic variability exhibits a range of PON1 expression different from other PON1 variants (15,18). PCBs were defined as the sum of congeners 118, 153, 138, and 180 (7).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that the level of PON1 in newborns is 3-4fold lower than the adults [18,19]. But as per our knowledge no study has been conducted so far showing the relation between birth weight and cord blood arylesterase and lactonase activity.…”
Section: Discussionmentioning
confidence: 90%